Calibration of the near-surface seismic structure in the SCEC community velocity model version 4. Issue 3 (10th May 2022) - Hu, Zhifeng; Olsen, Kim B; Day, Steven M
SUMMARY: The near-surface seismic structure (to a depth of about 1000 m), particularly the shear wave velocity ( V S ), can strongly affect the propagation of seismic waves and, therefore, must be accurately calibrated for ground motion simulations and seismic hazard assessment. The V S of the top (<300 m) crust is often well characterized from borehole studies, geotechnical measurements, and water and oil wells, while the velocities of the material deeper than about 1000 m are typically determined by tomography studies. However, in depth ranges lacking information on shallow lithological stratification, typically rock sites outside the sedimentary basins, the material parameters between these two regions are typically poorly characterized due to resolution limits of seismic tomography. When the alluded geological constraints are not available, models, such as the Southern California Earthquake Center (SCEC) Community Velocity Models (CVMs), default to regional tomographic estimates that do not resolve the uppermost V S values, and therefore deliver unrealistically high shallow V S estimates. The SCEC Unified Community Velocity Model (UCVM) software includes a method to incorporate the near-surface earth structure by applying a generic overlay based on measurements of time-averaged V S in top 30 m ( V S30 ) to taper the upper part of the model to merge with tomography at a depth of 350 m, which can be applied to any of the velocity models accessible through UCVM. However, our 3-D simulations of the 2014 M w 5.1 La Habra earthquake in the Los Angeles area using the CVM-S4.26.M01 model significantly underpredict low-frequency (<1 Hz) ground motions at sites where the material properties in the top 350 m are significantly modified by the generic overlay ('taper'). On the other hand, extending the V S30 -based taper of the shallow velocities down to a depth of about 1000 m improves the fit between our synthetics and seismic data at those sites, without compromising the fit at well-constrained sites. We explore various tapering depths, demonstrating increasing amplification as the tapering depth increases, and the model with 1000 m tapering depth yields overall favourable results. Effects of varying anelastic attenuation are small compared to effects of velocity tapering and do not significantly bias the estimated tapering depth. Although a uniform tapering depth is adopted in the models, we observe some spatial variabilities that may further improve our method.